Industrial Disputes, Causes and Settlement: An Indian Perspective - Maria Jesili, I. (Prabandhan: Indian Journal of Management, 2012)
An industrial dispute is a manifestation of a disagreement and a difference of opinion between the two disputants, namely the employer and the workmen. The potential for conflicts exist in all human situations and organizations. A passive and subdued workforce is not conducive for good relationships. The relationships in the industrial relations system start with cooperation, soon change between the two into conflicts, and after they are resolved, change again into one of cooperation. This changing process is a continuous feature of the industrial relations system. Industrial disputes arise due to various causes, which may be classified into economic, organizational, physical, technical, political, psychological and market-oriented conditions. The workers are especially interested in higher wages, congenial working conditions, and opportunities for career advancement, welfare facilities, job satisfaction and the like. When these are denied to them, the workers are forced to assert their rights, which then lead to industrial disputes. In the present economic scenario, there is a situation of rising input costs and declining output prices. Productivity improvement becomes imperative even to maintain the existing levels of profitability. The resultant squeeze in employment, wages, dearness allowance, bonus and benefits create a sense of helplessness and result in disputes in the industrial setup. The present research paper analyses the causes and settlement of disputes from the perspectives of both - the workers and the management and suggests measures for maintaining good relations between the management and the workmen. The Findings of the study show that bonus, wages and allowances are the major causes responsible for industrial disputes from the perspective of both the workers and the management. Inter-union rivalry is the prime factor which influences disputes, and arbitration is the best way for the settlement of disputes.